Membrane-bound alkaline phosphatase from ectopic mineralization and rat bone marrow cell culture - Simao, Ana Maria. S.; Beloti, Marcio M.; Cezarino, Rodrigo M.; Rosa, Adalberto Luiz; Pizauro, Joao M.; Ciancaglini, Pietro (Elsevier B.V., 2007)
Cells from rat bone marrow exhibit the proliferation-differentiation sequence of osteoblasts, form mineralized extracellular matrix in vitro and release alkaline phosphatase into the medium. Membrane-bound alkaline phosphatase was obtained by method that is easy to reproduce, simpler and fast when compared with the method used to obtain the enzyme from rat osseous plate. The membrane-bound alkaline phosphatase from cultures of rat bone marrow cells has a MWr of about 120 kDa and specific PNPP activity of 1200 U/tng. The ecto-enzyme is anchored to the plasma membrane by the GPI anchor and can be released by PIPLC (selective treatment) or polidocanol (0.2 mg/mL protein and 1% (w/v) detergent). The apparent optimum pH for PNPP hydrolysis by the enzyme was pH 10. This fraction hydrolyzes ATP (240 U/mg), ADP (350 U/ mg), glucose 1-phosphate (1100 U/mg), glucose 6-phosphate (340 Wing), fructose 6-phosphate (460 U/mg), pyrophosphate (330 U/mg) and (3glycerophosphate (600 U/mg). Cooperative effects were observed for the hydrolysis of PPi and beta-glycerophosphate. PNPPase activity was inhibited by 0.1 mM vanadate (46%), 0.1 mM ZnCl2 (68%), 1 mM levamisole (66%), 1 mM arsenate (44%), 10 mM phosphate (21%) and 1 mM theophylline (72%). We report the biochemical characterization of membrane-bound alkaline phosphatase obtained from rat bone marrow cells cultures, using a method that is simple, rapid and easy to reproduce. Its properties are compared with those of rat osseous plate enzyme and revealed that the alkaline phosphatase obtained has some kinetics and structural behaviors with higher levels of enzymatic activity, facilitating the comprehension of the mineralization process and its function. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: Alkaline phosphatase; bone marrow; Osseous plate; cell culture; glycosyl phosphatidylinositol anchor (GPI); membrane solubilization; kinetic data; inhibition